Facile chemo-, regio-, and diastereoselective approach to cis-3,5-disubstituted gamma-butyrolactones and fused gamma-butyrolactones - Baag, Md. Merajuddin; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
Chemoselective S(N)2' condensation of primary enolates of alkyl methyl ketones 2a-e with dimethyl bromomethylfumarate ( 1) followed by highly diastereoselective NaBH4 reduction of the ketone function in the formed ketodiesters 3a-e and the regioselective in situ lactonization of the unisolable intermediates 4a-e exclusively furnished the cis-3,5-disubstituted gamma-butyrolactones (+/-)-5a-e in very good yields. Similarly, the face-selective coupling reaction of cyclohexanone enolate with 1 to form a mixture of diastereomers in an 8: 2 ratio followed by a highly selective reductive cyclization of 9 plus 10 exclusively provided the cis-octahydrobenzofuran (+/-)- 12 in 70% overall yield.

Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Synthesis of gymnoascolide A - Baag, Md. Merajuddin; N. P. Argade (Synthesis-Stuttgart, 2008)
Recently isolated 4-benzyl-3-phenylfuran-2,5-dione and antifungal gymnoascolide A have been synthesized using the chemoselective S(N)2' coupling of phenylmagnesium bromide with dimethyl 2-(bromomethyl)fumarate, chemoselective allylic substitution of bromide in 3-(bromomethyl)-4-phenylfuran-2,5-dione with phenylmagnesium bromide and regioselective N-Selectride-induced reduction of 3-benzyl-4-phenylfuran-2,5-dione as the key reactions.
Keywords: dimethyl (bromomethyl)fumarate; functionalized maleic anhydrides; gymnoascolide A; regioselective reduction; S(N)2 ` Grignard coupling reaction